Cultural Capital and Souvenir Product Development for Tourism Promotion in Long District, Phrae Province - Yuktirat, Chananchida; Panriansaen, Rattana; Phanthuwet, Chuangchot (Journal of Thai Hospitality and Tourism, 2025)
This research aimed to 1) study spatial data and collect data on cultural capital, arts and culture, and raw materials, as well as the craftsmen and craftsmanship in Long District, Phrae Province; 2) develop souvenir products for tourism promotion in Long District, Phrae Province, and assess the suitability of the concept and principle of souvenir product prototype development; and 3) assess the satisfaction with souvenir product prototypes for tourism promotion in Long District, Phrae Province. The three phases of the action plan were as follows. Phase 1 consisted of spatial data collection in Long District, Phrae Province by 16 key informants using nonprobability sampling, purposive sampling, snowball sampling, and secondary data sets. Phase 2 involved development, design, prototyping, and prototype evaluation by five experts in design. Finally, Phase 3 incorporated a prototype satisfaction appraisal by using a sample size from Yamane’s (1973) random sampling table, which was equal to 100 people ±10% error (E) when using a simple random sampling technique with a sample of males and females aged 22 years and over in Long District, Phrae Province. The research findings indicated that the sample was satisfied with the prototype overall, rating it as “very good” ( = 4.97, S.D. = 0.04) in the following areas: psychology and aesthetics, arts and culture, usability, shop location and distribution service management, and opinions on the development of souvenir products for tourism promotion in Long District, Phrae Province.